2000
DOI: 10.1590/s1020-49892000000800004
|View full text |Cite
|
Sign up to set email alerts
|

Microbial quality of water in rural communities of Trinidad

Abstract: A cross-sectional study was conducted in four rural communities of northeastern Trinidad to determine the microbial quality of water supply to households and that quality's relationship to source and storage device. Of the 167 household water samples tested, total coliforms were detected in 132 of the samples (79.0%), fecal coliforms in 102 (61.1%), and E. coli in 111 (66.5%). There were significant differences among the towns in the proportion of the samples contaminated with coliforms (P < 0.001) and E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 31 publications
1
23
2
1
Order By: Relevance
“…It has been reported that coliform can be found both in chlorinated and unchlorinated water and that their total elimination from water would require the knowledge of their population in such water and determining the quantity of chlorine needed for their complete chlorinators (Inyang, 2009). However, tap water are usually stored in storage devices such as tanks and reservoirs after harvesting and therefore, having unsanitary storage devices is known to contribute to substantial reduction in water quality (Welch et al, 2000). Members of the genus Staphylococci, mostly S. aureus is considered as an indicator of hygienic status employed in the field of production or distribution of drinking water (Mihdhdir, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that coliform can be found both in chlorinated and unchlorinated water and that their total elimination from water would require the knowledge of their population in such water and determining the quantity of chlorine needed for their complete chlorinators (Inyang, 2009). However, tap water are usually stored in storage devices such as tanks and reservoirs after harvesting and therefore, having unsanitary storage devices is known to contribute to substantial reduction in water quality (Welch et al, 2000). Members of the genus Staphylococci, mostly S. aureus is considered as an indicator of hygienic status employed in the field of production or distribution of drinking water (Mihdhdir, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium has no effect on human health in water, but it can cause hardness problem risk and directly related to hardness (Welch et al, 2000). Except for sample area from Alatayte2, Moriteta, Airport, Fasha town, Gersale and Fuchucha, rest of the samples' concentrations of calcium are above permissive standard limit prescribed by WHO.…”
Section: Determination Of Light and Heavy Metalsmentioning
confidence: 95%
“…Studies done to find out the bacteriological quality of the water used by some street vendors have revealed frequent contamination with coliforms and fecal coliforms [43]. When the street foods in Trinidad and Tobago were analyzed, it was reported found that 35% of foods were contaminated by E. coli while 57.5% of water used by vendors were contaminated by coliforms [26,[44][45][46]. These reports were similar to the findings that the stored water used by consumers and vendors, at the vending site, showed heavy bacteriological contamination of faecal origin [31].…”
Section: Watermentioning
confidence: 99%